STUDI KARAKTERISTIK FISIK DAN NYALA API BRIKET DAUN BAMBU - Ainurrofiq, Arif; Qiram, Ikhwanul (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2021)
Briquettes are solid fuels derived from biomass waste obtained from the compression of the shaped powdered material. This study aims to obtain the physical characteristics and flame characteristics of leaf briquettes of Javanese bamboo (Gigantochloa Apus) and ori bamboo (Bambusa Arundinacea). The method used in this research is varying the pressing load of 5 kg, 10 kg, 15 kg, and the size of the briquette powder (particles) of 20, 40, 60, a cylinder-shaped mold with a diameter of 38 mm and an inner hole diameter of 9 mm. The analysis includes the characteristics of the fire products (area, color and temperature) and the surface morphology of the briquettes. The pressing load affects the characteristics of the resulting flame. The results showed that the type of bamboo, the size of the biomass particles and the pressing load affected the characteristics of the flame.